2018
DOI: 10.1016/j.addma.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of in-situ distortion and bulging for an arbitrarily curved additive manufacturing directed energy deposition geometry

Abstract: With the recent rise in the demand for additive manufacturing (AM), the need for reliable simulation tools to support experimental efforts grows steadily. Computational welding mechanics approaches can simulate the AM processes but are generally not validated for AM-specific effects originating from multiple heating and cooling cycles. To increase confidence in the outcomes and to use numerical simulation reliably, the result quality needs to be validated against experiments for in-situ and post-process cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…To validate the path‐planning algorithms, a DED component was built using the zig‐zag and contour‐parallel tool‐path generation. The geometry was chosen to be a filled turbine blade cross‐section used already in thin‐walled form for prior investigations by Biegler et al [ 13 ] and is shown in Figure 6 .…”
Section: Methodsmentioning
confidence: 99%
“…To validate the path‐planning algorithms, a DED component was built using the zig‐zag and contour‐parallel tool‐path generation. The geometry was chosen to be a filled turbine blade cross‐section used already in thin‐walled form for prior investigations by Biegler et al [ 13 ] and is shown in Figure 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Biegler et al [ 73 ] presented a new approach based on full-field measurements to experimentally quantify the distortions of parts obtained by laser metal deposition (LMD) AM. Moreover, full-field data were used to validate the numerical simulation of the AM process [ 74 ]. In this case, the in situ DIC measurements were advantageously applied to measure distortions on the wall geometry produced by LMD.…”
Section: In Situ Monitoring Of Am Using Dicmentioning
confidence: 99%
“…These numerical models can be relevant to predict the mechanical behaviour of parts during the manufactured process itself. Biegler et al [ 74 ] validated a structural thermomechanical simulation model in a direct energy deposition (DED) part using in situ measurements. The validation of an elasto-plastic finite element model for the deposition of directed energy from AM was shown in an arbitrarily curved geometry.…”
Section: In Situ Monitoring Of Am Using Dicmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous attempts have been made to develop the thermo-mechanical numerical model and experimental validation for the DED process using the weld model [ 15 ]. A limited resource was reported in optimizing computational time for the DED process considering a large number of layers in the printed sample.…”
Section: Introductionmentioning
confidence: 99%